Colonic perforation following mild abdominal trauma in a patient with Crohn's disease: a case report - Bunni, John (BioMed Central, 2008)
Colonic perforation following mild abdominal trauma in patients with Crohn's disease is a rare occurrence. We present a case of a 21 year old Crohn's sufferer, who presented to the emergency department with signs of shock and peritonitis following minor abdominal trauma. A computed tomography (CT) scan revealed ascending colonic perforation and he underwent a subsequent right hemicolectomy. This is the first UK report of a patient with inflammatory bowel disease suffering colonic perforation following minimal trauma.